In between the "brows" - Ursulesku, Oana (ELOPE (Ljubljana), 2016)
The global phenomenon of popular music from the middle of the twentieth century on played a pivotal role in the merging of what was traditionally deemed high and low cultures. Performers of popular music of different genres started including direct references to literary works from the Anglo-American literary canon, one of the most famous examples being Kate Bush's 1989 single "The Sensual World" in which she originally intended to quote verbatim from Molly Bloom's soliloquy Bloom in James Joyce's Ulysses; however, since permission from the Joyce Estate was not granted, the song did get recorded, but with lyrics that Bush wrote herself, inspired by Molly Bloo's words on the page. This paper analyses the way ideas from the original literary work get transposed and adapted in the lyrics of the popular song, giving credit to the musicians as not only innovative creators of a new work of art, but creators of an adapted work of art that can be intertextually read in the context of the artist's cultural heritage.
Keywords: adaptacija; književnost; literature; popularna kultura; rock glasba